The ecology of the sable antelope Hippotragus niger niger (Harris 1838) in the Masebe Nature Reserve, Lebowa - Van Aarde, Rudi J. (University of Pretoria, 2022)
Dissertation (MSc (Zoology))--University of Pretoria, 1991.